Analysis of Factors Affecting the Development Status of Toddlers in Simomulyo Health Center Surabaya - Dyah Aisyah Rachmawatie; Farida Fitriana; Martono Tri Utomo; Pudji Lestari (Rifa'Institute, 2022)
Background: Development is one of the important things for the future of a child. The most crucial development occurs during the first five years of a child's life, this time is often called the golden period. At this time all the development of children must be by their age so that in the future there are no developmental delays. A child's development can be influenced by several factors, both internal and external factors. Based on previous research as many as 5-10% of Indonesian children experience general developmental delays, so the development of Indonesian children still requires serious attention. Therefore, this study aims to analyze factors that affect the development status of toddlers. Method: This study is an observational analytical study using a cross-sectional approach. With a sample number of 100 toddlers in the working area of Simomulyo Health Center that meets the criteria of inclusion and uses consecutive sampling techniques. Independent variables in the study were birth weight, nutritional status of toddlers, parents' last education, economic status, history of disease in toddlers, and history of exclusive breast milk. While the dependent variable in this study is the status of development. The chi-square statistical test is used to determine the significant level of data obtained at the meaningful level of ? =0.05. Results: The results of the study found 90% experienced appropriate developmental status, 86% had normal nutritional status based on BB / U, 45% had normal nutritional status based on TB / U, 64% had normal nutritional status based on BB / TB, 82% of toddler parents had the last high education, 67% of toddlers have economic status ?UMR, 50% of toddlers have a history of pain ?2 times sick and 56% of toddlers get exclusive breast milk ?6 months. From the results of statistical tests chi-square obtained birth weight ? = 0.444 (??0.05), nutritional status based on BB / U ? = 0.578 (??0.05), nutritional status based on TB / U ? = 0.375 (??0.05), nutritional status based on BB / TB ? = 0,706 (??0.05), parental education ?=0.488 (??0.05), economic status ?=0.103 (??0.05), history of childhood disease ?=0.046 (?<0.05), exclusive breast milk history ?=0.002 (?<0.05). It means that there is no relationship between developmental status with birth weight, nutritional status, parents' last education, economic status. However, there is a relationship between developmental status and a history of toddler disease, and a history of exclusive breast milk. Conclusion: A toddler's history of disease and a history of exclusive breast milk have relationships that can affect a toddler's development.